Cranial MRI scans are indicated in all girls with central precocious puberty. Issue 5 (1st May 2003) - Ng, S M; Kumar, Y; Cody, D; Smith, C S; Didi, M
Abstract : Aims: (1) To assess the value of cranial magnetic resonance imaging (MRI) scans in the investigation of girls with central precocious puberty (CPP); and (2) to determine the clinical predictors of abnormal cranial MRI scans in these patients. Methods: A retrospective study of 67 girls diagnosed with CPP who underwent cranial MRI scans at diagnosis. Patients with neurological signs or symptoms at presentation were excluded. Results: The mean age of onset of puberty was 6.2 years (range 2.0–7.9). Intracranial abnormalities were present in 10 (15%) patients (MR + ), while 57 (85%) had no abnormalities (MR − ). There was no statistical difference between MR + patients and MR − patients at presentation with respect to age of onset of puberty, pubertal stage, bone age advance, pelvic ultrasound findings, or height or body mass index standard deviation scores (SDS). Conclusion: Girls with CPP should have a cranial MRI scan as part of their assessment since clinical features, including age, are not helpful in predicting those with underlying pathology. Implementation of such an approach may have a substantial effect on clinical practice and healthcare cost.